The Catholic Sexual Abuse Crisis as a Theological Crisis Emerging Issues - Faggioli, Massimo 1970- (2019)
The sexual abuse crisis has long-term consequences: not only on the victims and survivors of abuse, but also on the theological standing and balance of the Catholic Church throughout the world. Theological rethinking in light of the abuse crisis is necessary: not only from the lens of those who have suffered, but also from the lens of the changes caused by this global crisis in the history of the whole Catholic community. The article examines the consequences of the abuse crisis on different theological disciplines, with particular attention to the history of the Catholic Church, liturgy, ecclesiology of reform, and church-state relationships.
Keywords: church-state relations; Ecclesiology; episcopalism; Liturgy; Reform; Sexual Abuse; theology of childhood